2019
DOI: 10.1111/cfs.12637
|View full text |Cite
|
Sign up to set email alerts
|

“Power together”: Professionals and parents of children with disabilities creating productive partnerships

Abstract: Disparity of power and authority in the relationship between parents and professionals has been shown to be a major challenge in creating a successful partnership in caring for children with disability. The goal of this article was to evaluate workshops attended by professionals and parents of children with disability by raising awareness to barriers related to incompatible expectations and role definitions. The research explored the experiences of the participants in order to identify factors that facilitated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Implications for Future Study. While parents of children with disabilities may benefit from involvement in coproduction processes, they tend to experience unique barriers to doing so (Cohen & Mosek, 2019). Government policy has a critical role in generating the conditions under which families of children with disabilities participate in coproduction processes.…”
Section: Implications For Family-centered Services In Times Of Emergencymentioning
confidence: 99%
“…Implications for Future Study. While parents of children with disabilities may benefit from involvement in coproduction processes, they tend to experience unique barriers to doing so (Cohen & Mosek, 2019). Government policy has a critical role in generating the conditions under which families of children with disabilities participate in coproduction processes.…”
Section: Implications For Family-centered Services In Times Of Emergencymentioning
confidence: 99%
“…Research on the ways that families adjust to disabled family members has been developed since 1950s and sustained till the present time (Cohen and Mosek 2019 ; Seligman 1999 ). Early studies affirmed that family members were thought to be devastated by childhood disability (McCabe 2007 ; Neely-Barnes and Dia 2008 ).…”
Section: Theoretical Background: ‘Othering’ and Family-based Violencementioning
confidence: 99%
“…However, based on reports and research mostly conducted in the Western countries, in contemporary times, children with disabilities and their families basically function well (Cohen and Mosek 2019 ). This functioning has been largely attributed to the availability of medical and social support provisions to children with disability and their parents (Mas et al 2019 ).…”
Section: Theoretical Background: ‘Othering’ and Family-based Violencementioning
confidence: 99%
“…Czy _ z (2017) suggested that parents can benefit from taking an active role in providing support to encourage the capabilities of their children. Additionally, Cohen and Mosek (2019) cited that parents regard "trust" as the most important component when creating partnerships with professionals. Parents trained to understand their child's development and emotional needs is encouraged during early stages of development (Thwala et al, 2015) within a strengths-based approach.…”
Section: Experiences Of Parentsmentioning
confidence: 99%